2014
DOI: 10.4238/2014.february.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D with asthma and COPD: not a false hope? A systematic review and meta-analysis

Abstract: ABSTRACT. Vitamin D deficiency and insufficiency are increasingly being recognized in the general population over the last few decades. However, a number of other disorders have now been linked to vitamin D deficiency and insufficiency, including asthma and COPD. The aim of this study was to evaluate the evidence on the effect of vitamin D on asthma and COPD. We searched electronic databases including SCI, EMBASE, Ovid, and PubMed. Reviewers working independently and in duplicate extracted study characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…In COPD patients, a weak relationship was observed between serum vitamin D and FEV1/FVC 36 . This is more likely due to less sample size 37 . Vitamin D has an anti-inflammatory effect that can be modified by exposure to cigarette smoke 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In COPD patients, a weak relationship was observed between serum vitamin D and FEV1/FVC 36 . This is more likely due to less sample size 37 . Vitamin D has an anti-inflammatory effect that can be modified by exposure to cigarette smoke 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two meta-analyses were conducted to assess the association between vitamin D and COPD. Zhang et al15 just included two studies, and no statistical significance was found in the analysis. Zhu et al16 conducted a meta-analysis of 18 studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusion was not definite. Two meta-analyses on the roles of vitamin D in COPD have been conducted 15,16. However, the studies did not include enough articles, did not extract correct data, pooled the levels of vitamin D from serum and plasma, included participants with vitamin D supplement, or did not analyze the sources of high heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 There are several risk factors associated with COPD in later life, such as smoking, diabetes, and vitamin D deficiency. 6 8 Since COPD is associated with increased early mortality compared with general population, development of new treatments aiming to prolong their lives is important. In addition, identification of clinical characteristics predicting mortality is also helpful to improve the efficacy of current treatments for an individual patient.…”
Section: Introductionmentioning
confidence: 99%